Heart-type fatty acid binding protein level in familial Mediterranean fever - Özlem Karakurt Arıtürk; Kemal Üreten; Münevver Sarı; Nuray Yazıhan; Evin Yılmaz; İmge Ergüder (KARE Publishing, 2013)
Objectives: Familial Mediterranean fever (FMF) is an autosomal recessive disorder and the most frequent periodic syndrome characterized by recurrent attacks of polyserositis. Heart-type fatty acid-binding protein (h-FABP) is an intracellular molecule engaged in the transport of fatty acids through the myocardial cytoplasm and a rapid marker of myocardial injury. FMF is an autoinflammatory disease characterized by ongoing inflammatory activity. Inflammation also plays an important role in the development and progression of atherosclerosis in some rheumatic diseases. We aimed to investigate markers of atherosclerosis in patients with FMF by the measurement of serum h-FABP and malondialdehyde levels (MDA). Study design: Forty consecutive patients with FMF and twenty healthy volunteers were selected to participate in the study. The diagnosis of FMF was based on Tel-Hashomer criteria. Serum h-FABP and MDA levels were determined to examine the association. Results: The mean h-FABP level in FMF patients was significantly higher than the normal population (4.89+-0.83 vs. 3.06+-2.13 ng/ml, p<0.01). The mean platelet volume was significantly higher in FMF patients than in the normal group (8.87+-0.99 vs. 8.22+-0.45 fl, p=0.04). Serum MDA levels were the same between the groups (1.08+-0.66 vs. 1.08 +- 0.33 nmol/ ml, p=0.99). h-FABP and MDA levels were the same in FMF patients with an acute attack and during an attack free period. Conclusion: Our results show that h-FABP increases in patients with FMF. Higher h-FABP levels may lead to increased atherosclerotic propensity in FMF, independent of the oxidative stress status of these patients.